Tathbiqu Kitabi “Taqribu An Nahwi Wa As Shorfi” Fi Ta’limi An Nahwi Wa As Shorfi Bi Ma’hadi Barakah Al ‘Ulum Kajen – Pati Jawa Tengah 2021/2022 - Salafuddin; Toto Suharto (Rayah Al-Islam, 2022)
أهداف هذا البحث لمعرفة كيفية تطبيق تعليم النحو والصرف باستخدام كتاب "تقريب النحو والصرف" ومعرفة العوامل الدافعة والعوائقة عن استخدام كتاب "تقريب النحو والصرف" بمعهد بركات العلوم حاجين – باطي جاوي الوسطى سنة 2021/2022.هذا البحث هو البحث الوصفى النوعي, يقع في المعهد بركات العلوم حاجين-باطي, جاوي الوسطى, بدأ من شهر فبرايير إلى أبريل 2022. موضوع البحث هو مدرس تعليم النحو والصرف والطلبة. أما جمع البينات بطريقة الملاحظة والمقابلة والتتوثيقي. وأما صدق البينات بطريقة التثليث المصادر. ثم تحليل البينات بطريقة إطلاع البيانات من عدة المصادر.وتشير نتائج البحث إلى أن: (1) تلعب المواد التعليمية في أنشطة تعليم القواعد النحوية والصرفية باستخدام كتاب تقريب النحو والصرف, دورًا مهمًا للغاية. يقدم هذا الكتاب للمرحلة المبتدئين ليكونوا قادرين على قراءة كتب التراث، وخاصة كتاب فتح القريب. (2) طريقة عملية التعليم القواعد النحوية والصرفية باستخدام كتاب تقريب النحو والصرف, هي: طريقة الاستقرائية وأيضا بالطريقة الإبتدائية, وطريقة الأسئلة و الأجوبة. (3) التقييم في تطبيق الكتاب تقريب النحو والصرف بثلاث طرق: اختبار شفهي, اختبار كتابي, اختبار عملي. (4) العوامل الدافعة في هذه التعليمية, وهي: أهداف التعليمية بهذا الكتاب واضحة ومنهجية,و مواد تعليمية بسيطة وقابلة للتطبيق, واستخدام أمثلة من كتاب تقريب (فتح القريب), تستخدم الصيغ التي تمت دراستها دائمًا في المواد اللاحقة, ويمكن للطلاب أن يكونوا مدرسين لأصدقائهم, وينتهي كل فصل وفصل فرعي في المادة بتقييم واضح. فأما العوامل العوائقة هي: عمل التعليم كل أسبوع بلقاء واحد فقط, ويجد الطلاب صعوبة في الحفظ, ويشعر الطلاب أحيانًا بالملل من الحفظ المتكرر, ولا توجد مبادئ توجيهية أو مبادئ توجيهية في تدريس المادة في هذا الكتاب، ولا يفهم الطلاب بعمق حول نظرية وقواعد اللغة العربية، ومطلوب فهم كاف لقواعد اللغة العربية والإندونيسية، لأن شرح المادة يستخدم نهجًا تباينًا, ونادر استخدام أمثلة من كتاب أخر, وأن كتاب تقريب النحو والصرف لا يزال كتابًا جديدًا يتم تطبيقه في المعهد الأخر. The purpose of this study was to find out how the application of Nahwu and Shorf learning using the "Taqrib an-Nahwi wa ash-Shorfi" book and to find out the supporting and inhibiting factors for the use of the "Taqrib an-Nahwi wa ash-Shorfi" book at the Barakatul Ulum Kajen Islamic Boarding School, Pati, Central of Java in 2021/2022. This research is a qualitative descriptive study, taking place at the Barakatul Ulum Kajen Islamic Boarding School, Pati. This research started from February to April 2022. The research subjects were Nahwu and Shorf teachers and students. The data collection are observation, interview and documentation. The proof of the data is done by data triangulation method. Then analyze the data by informing it from several sources. The results of the study show that: (1) The material in Nahwu and Shorf learning activities using the book "Taqrib an-Nahwi wa ash-Shorfi" plays a very important role. This book is intended for beginners to be able to read turats books, especially the book Fath al-Qorib. (2) The method in this learning is the istiqro'iyyah method, the ibtida'iyyah method, and the question and answer method. (3) Evaluation in the application of the Book of "Taqrib an-Nahwi wa ash-Shorfi" in three ways: oral test, written test, and practical test. (4) The driving factors in this education, namely: the purpose of education in this book is clear and systematic, and the teaching materials are simple and applicable, and the use of examples from the book of Taqrib (Fath al-Qarib), the formulas that have been studied are always used in the next subject, and students can become teachers for their friends, each chapter and sub-chapter in this learning ends with a clear assessment. The inhibiting factors include: there is only one meeting in a week, there are some students who have a little difficulty in memorizing, students sometimes get bored with frequent memorization, there are no guidelines in teaching the material in this book, and students do not yet understand deeply about theory and grammar. In the Arabic language, sufficient understanding of Arabic and Indonesian grammar is required, because the explanation of the material uses the mother tongue approach (Indonesian), examples from other books are rarely used, and the book "Taqrib an-Nahwi wa ash-Shorfi" is still classified a new book that rarely implemented in other institution.